NORMAL DOCUMENTS ACCEPTED IN THE FIELD OF ARCHIVE WORK IN UZBEKISTAN AND THEIR SIGNIFICANCE - Khushmatova Sarvinoz Bahodir kizi (American Journals Publishing, 2023)
This article talks about the normative documents adopted in the field of archival work in Uzbekistan and their importance. Based on archival data, the author analyzed the problem on the basis of available scientific literature and studied the existing specific aspects of the normative documents adopted in the field of archival work in Uzbekistan and their importance.
Keywords: Uzbekistan, archives, archival documents, funds, normative documents.